2017
DOI: 10.3389/fmicb.2017.01729
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Communities Including Plant Pathogens in Near Surface Air Are Similar across Northwestern Europe

Abstract: Information on the diversity of fungal spores in air is limited, and also the content of airborne spores of fungal plant pathogens is understudied. In the present study, a total of 152 air samples were taken from rooftops at urban settings in Slagelse, DK, Wageningen NL, and Rothamsted, UK together with 41 samples from above oilseed rape fields in Rothamsted. Samples were taken during 10-day periods in spring and autumn, each sample representing 1 day of sampling. The fungal content of samples was analyzed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 37 publications
8
55
1
Order By: Relevance
“…S3), with the fungal community usually less diverse in the middle of the summer (July) than at the beginning (end of spring) and the end (beginning of autumn) of the growing season. The temporal heterogeneity in the fungal communities was also observed by Nicolaisen et al ( 56 ) in northwestern Europe and was often attributed to nutritional demands and survival strategies. Surrounding vegetation is particularly important for the life cycles of some plant-pathogenic fungi that are associated with particular crop or plant growth stages ( 57 ).…”
Section: Discussionsupporting
confidence: 69%
“…S3), with the fungal community usually less diverse in the middle of the summer (July) than at the beginning (end of spring) and the end (beginning of autumn) of the growing season. The temporal heterogeneity in the fungal communities was also observed by Nicolaisen et al ( 56 ) in northwestern Europe and was often attributed to nutritional demands and survival strategies. Surrounding vegetation is particularly important for the life cycles of some plant-pathogenic fungi that are associated with particular crop or plant growth stages ( 57 ).…”
Section: Discussionsupporting
confidence: 69%
“…This result does not affect the global ratio of BMC/AMC (e.g., Figure 7) but points out (1) the importance to consider BMC/AMC ratios by season for one given ecosystem and (2) to have a better understanding of the BMC/AMC ratio as a function of environmental considerations as proposed by [15]. In 2017, [72] showed similar and finer results regarding the seasonality of BMC/AMC using DNA analysis in several northern Europe locations and the observations suggested that the biodiversity of fungal spores can be observed after 900 km from an ecosystem to another one with consequences on the variation in the BMC/AMC ratios. BMC/AMC ratios by season for one given ecosystem and (2) to have a better understanding of the BMC/AMC ratio as a function of environmental considerations as proposed by [15].…”
Section: Seasonality Of Bmc and Amcmentioning
confidence: 86%
“…BMC/AMC ratios by season for one given ecosystem and (2) to have a better understanding of the BMC/AMC ratio as a function of environmental considerations as proposed by [15]. In 2017, [72] showed similar and finer results regarding the seasonality of BMC/AMC using DNA analysis in several northern Europe locations and the observations suggested that the biodiversity of fungal spores can be observed after 900 km from an ecosystem to another one with consequences on the variation in the BMC/AMC ratios. In the literature it has been found that emissions of fungal spores from the oceans (10 Mg per year) are several orders of magnitude smaller than from inland surfaces Tg per year) [18,19].…”
Section: Seasonality Of Bmc and Amcmentioning
confidence: 99%
“…Work is currently in progress to improve the taxonomic resolution of these tools to genus or species level. Whilst there appears to be little literature about the use of metabarcoding for plant pathology but it has been used to analyse fungal pathogens of olive (Abdelfattah et al 2015) to track a range of pathogens in air samples (Nicolaisen et al 2017), bacteria in vineyards (Burns et al 2015), and plant pathogenic nematodes (Ahmed et al 2015).…”
Section: Early Surveillancementioning
confidence: 99%